Influence of sports compression textiles on endurance running performance - Harnisch, M.; Klepser, A.; Classen, E.; Beringer, J.; Schmidt, A. (Extreme Physiology & Medicine, 2015)
Introduction: Sports compression textiles are very popular, especially in endurance sports like triathlon and marathon running. It is well known, that medical compression stockings reduce the expansion of veins and a compressive gradient to the heart enhances venous blood flow. During sports compressive textiles reduce wobbling masses, muscle vibration and swelling. Therefore compression should lead to better endurance performance, but the benefit on endurance performance is not clearly proved, e.g. Kemmler et al. found a benefit by compression textiles while Sperlich et al. did not.